Crystal structure of the uranyl arsenate mineral hügelite, Pb2(UO2)3O2(AsO4)2(H2O)5, revisited: a correct unit cell, twinning and hydrogen bonding - Plášil, Jakub; Petříček, Václav; Škácha, Pavel (Acta crystallographica Section B, Structural science, crystal engineering and materials, 2021)
Revisiting the structure of uranyl arsenate mineral hügelite provided some corrections to the available structural data. The previous twinning model (by reticular merohedry) in hügelite has been corrected. Twinning of the monoclinic unit cell [a = 7.0189 (7) Å, b = 17.1374 (10) Å, c = 8.1310 (10) Å and β = 108.904 (10)°], which can be expressed as a mirror in [100], leads to a pseudo-orthorhombic unit cell (a = 7.019 Å, b = 17.137 Å, c = 61.539 Å and β = 90.02°), which is eight times larger, with respect to the unit-cell volume, than a real cell. Moreover, the unit cell of chosen here and the unit cell given by the previous structure description both lead to the same supercell. A new structure refinement undertaken on an untwinned crystal of hügelite resulted in R = 4.82% for 12 864 reflections with Iobs > 3σ(I) and GOF = 1.12. The hydrogen-bonding scheme has been proposed for hügelite for the first time.
Keywords: crystal structure; uranyl arsenate; JANA2006; twinning; reticular merohedry; hügelite